Cervical Lymph Node Metastases from Central Nervous System Tumors: A Systematic Review - Coca-Pelaz, Andres; Bishop, Justin A.; Zidar, Nina; Agaimy, Abbas; Mello Santiago Gebrim, Eloisa Maria; Mondin, Vanni; Cohen, Oded; Strojan, Primoz; Rinaldo, Alessandra; Shaha, Ashok R.; De Bree, Remco; Hamoir, Marc; et al. (Cancer Management and Research, 2022)
Introduction: Lymph node metastasis (LNM) from primary tumors of the central nervous system (CNS) is an infrequent condition, and classically it was thought that CNS tumors could not spread via the lymphatic route. Recent discoveries about this route of dissemination make its knowledge necessary for surgeons and pathologists to avoid delays in diagnosis and unnecessary treatments. The aim of this paper is to review the literature and to discuss the relevant pathogenetic mechanism and the cytologic features along with recommendations for surgical treatment of these cervical LNM. Materials and Methods: Using PRISMA guidelines, we conducted a systematic review of the literature published from 1944 to 2021, updating the comprehensive review published in 2010 by our group. Results: Our review includes data of 143 articles obtaining 174 patients with LNM from a primary CNS tumor. The mean age of the patients was 31.9 years (range, 0.1-87) and there were 61 females (35.1%) and 103 males (59.2%), and in 10 cases (5.7%) the gender was not specified. The more frequent sites of distant metastasis were bones (23%), lungs (11.5%) and non-cervical lymph nodes (11%). Conclusion: Cervical LNM from CNS tumors is infrequent. Pathologic diagnosis can be obtained by fine-needle aspiration cytology in most cases, giving surgeons the option to plan the appropriate surgical treatment. Given the poor prognosis of these cases, the most conservative possible cervical dissection is usually the treatment of choice.
CRIS-Team WoS Importer:2022-03-25